The Impact of The Investment Opportunity Set on Dividends: An Effect of Sustainable Growth Rate - Junaidi Junaidi; Noorlailie Soewarno; Isnalita Isnalita (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose:  This research aims to examine dividends per share as a consequence of the investment opportunity set. Furthermore, research observes that, at a high level of sustainable development, the influence of investment opportunities on dividends per share changes. Methodology/approach: The sample consists of public companies from 1995 to 2023 in six ASEAN countries. A panel data set consisting of 65,239 observations was tested using variance-covariance error (VCE-Robust). Findings: The results of this research conclude that dividend per share is a consequence of the investment opportunity set. At a high level of sustainable development, the influence of investment opportunities on dividends per share changes negatively. Practical implications: When SGR is high, companies may be better off retaining earnings to finance investments rather than distributing them as dividends, because investments are more important for supporting long-term growth. Originality/value: The findings reveal novel dynamics, including the counterintuitive negative impact of high SGR on this relationship. The study provides context-specific insights that extend theoretical frameworks and offer actionable strategies for corporate decision-makers in emerging economies.